The Brendan voyage - Severin, Timothy (London : Abacus, 1996)
In 1976, Tim Severin and a crew of four men, set out to recreate the legendary sixth century voyage of St Brendan from Ireland to America. Their voyage across the Atlantic in a medieval boat made of leather, is one of the most hazardous and inspiring expeditions in the history of exploration.
Keywords: v; Ocean travel; Atlantic Ocean -- Description and travel